â€˜AlÄmÄt at-TarqÄ«m fÄ« KitÄb al-Lughah al-â€˜Arabiyyah bi Indonesia (Taá¸¥lÄ«l al-Akhá¹Ä' min al- KitÄb al-Muqarrar lil-Faá¹£l al-SÄbiâ€™ fÄ« al-Mará¸¥alah al-Mutawassiá¹ah) - Faiqoh, Putri Kholida (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This research aimed to identify the errors in the use of punctuations in the Arabic lesson book for 7th-grade students of Islamic Junior High School published by the Ministry of Religious Affairs Republic of Indonesia. This book is good, and it pays great attention to the writing rules of hamzah, tanwin, mad letters, and tasydid. However, the researcher found many errors in the use of punctuation marks. Thus, on the findings, it is expected that there will be more attention and improvement afterward. This research is descriptive qualitative research by the following error findings: exclamation mark (!), period (.), comma (,), question mark (?), brackets (), quotation marks â€œâ€¦ â€œ, hyphen (-), and slash (/). First, the error is in its use in sentences, and the placement of spaces as the bookâ€™s author follows the rules of Indonesian punctuation. Second, some texts only use periods (.) and commas () due to the authorâ€™s lack of knowledge of Arab and world culture, and he focuses only on mufradat. Third, there are reading texts that do not follow the instructions of the Rekon Text.ÙŠÙ‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ø§Ù„ØªÙ‘Ø¹Ø±Ù‘Ù Ø¹Ù„Ù‰ Ù†ÙˆØ¹ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ ÙÙŠ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø¹Ù„Ø§Ù…Ø§Øª Ø§Ù„ØªÙ‘Ø±Ù‚ÙŠÙ… ÙÙŠ Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ù…Ù‚Ø±Ù‘Ø±Â Ù„Ù„ÙØµÙ„ Ø§Ù„Ø³Ù‘Ø§Ø¨Ø¹ Ù„Ù„Ù…Ø±ØÙ„Ø© Ø§Ù„Ù…ØªÙˆØ³Ù‘Ø·Ø© Ø§Ù„Ù‘ØªÙŠ Ø£ØµØ¯Ø±Øª Ø¨Ù‡ ÙˆØ²Ø§Ø±Ø© Ø§Ù„Ø´Ù‘Ø¤ÙˆÙ† Ø§Ù„Ø¯Ù‘ÙŠÙ†ÙŠÙ‘Ø© Ø¨Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§. Ù‡Ø°Ø§ Ø§Ù„ÙƒØªØ§Ø¨ Ø¬ÙŠÙ‘Ø¯ ÙˆÙ…Ù‡ØªÙ…Ù‘ Ø¨Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù…Ø²Ø§Øª ÙˆØ§Ù„ØªÙ‘Ù†ÙˆÙŠÙ† ÙˆØØ±ÙˆÙ Ø§Ù„Ù…Ø¯Ù‘ ÙˆØ§Ù„ØªÙ‘Ø´Ø¯ÙŠØ¯. ÙˆÙ„ÙƒÙ†ØŒ ÙˆØ¬Ø¯Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø£Ø®Ø·Ø§Ø¡ ÙƒØ«ÙŠØ±Ø© ÙÙŠ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø¹Ù„Ø§Ù…Ø§Øª Ø§Ù„ØªÙ‘Ø±Ù‚ÙŠÙ…. ÙˆÙ…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ù†Ù‘ØªØ§Ø¤Ø¬ØŒ Ø±Ø¬Ø§Ø¡ Ø§Ù„Ù…Ø²ÙŠØ¯ Ù…Ù† Ø§Ù„Ø§Ù‡ØªÙ…Ø§Ù… ÙˆØ§Ù„ØªÙ‘ØØ³ÙŠÙ† Ø¨Ø¹Ø¯Ù. Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø¨ØØ« ÙˆØµÙÙŠÙ‘ Ù…Ù† ØÙŠØ« Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„ØªÙ‘Ø§Ù„ÙŠØ©: Ø¹Ù„Ø§Ù…Ø© Ø§Ù„ØªÙ‘Ø¹Ø¬Ù‘Ø¨ (!)ØŒ Ø§Ù„Ù†Ù‘Ù‚Ø·Ø© (.)ØŒ Ø§Ù„ÙØ§ØµÙ„Ø© (ØŒ)ØŒ Ø¹Ù„Ø§Ù…Ø© Ø§Ù„Ø§Ø³ØªÙÙ‡Ø§Ù… (ØŸ)ØŒ Ø§Ù„Ù‚ÙˆØ³Ø§Ù† ()ØŒ Ø¹Ù„Ø§Ù…Ø© Ø§Ù„Ø§Ù‚ØªØ¨Ø§Ø³